2018
DOI: 10.17759/exppsy.2018110401
|View full text |Cite
|
Sign up to set email alerts
|

Features of learning in toads Bufo viridis during behavior that requires taking into account the limits of their own bodies

Abstract: The goal of this work was to study the ability of the green toad Bufo viridis to form skills based on tactile sensations arising in the process of interaction between animal’s body and external objects. During the experiment we varied the proportions of the holes in the experimental setup, through which the animal penetrated, and the limits of the animal bodies by attaching blankets to their body with an extraneous object. It was found that toads can to take into account the natural limits of their own body wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In similar studies conducted on skinks, it was found that these animals are also able to take into account both natural and artificially increased (using objects attached to their heads) limits of their body when choosing a suitable hole to reach the lure [55]. Amphibians (European green toads) are able to take into account only the natural, but not artificially increased, limits of their bodies when solving an escape task [56].…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies conducted on skinks, it was found that these animals are also able to take into account both natural and artificially increased (using objects attached to their heads) limits of their body when choosing a suitable hole to reach the lure [55]. Amphibians (European green toads) are able to take into account only the natural, but not artificially increased, limits of their bodies when solving an escape task [56].…”
Section: Discussionmentioning
confidence: 99%
“…В ходе наших исследований, проводившихся с 2004 г., мы изучали феномен body-awareness у различных видов животных (Хватов, 2011;Хватов и др., 2016а, 2016б;Хватов, Желанкин, 2018;Khvatov et al, 2019). Животные решали задачу на соотнесение границ собственного тела с размерами отверстий в экспериментальной установке для проникновения в определенный отсек.…”
Section: методические проблемы исследования самосознания животныхunclassified